PMM.87 Successful Treatment of Early Antenatal Severe Resistant Hypertension by Bilateral Renal Angioplasty. (9th June 2014) - Sarween, N; Karim, A; Day, C; Lipkin, G; McCafferty, I; Temperton, D; Knox, E
Abstract : Background: Fibromuscular dysplasia (FMD) is the most frequent cause of renovascular hypertension in women of fertile age. We present a 36 year old identified in early pregnancy with severe resistant hypertension caused by bilateral FMD. Case: A 36-year-old primigravida with no past medical history was referred to the renal-obstetric services at 11 weeks gestation with severe hypertension. Mean ambulatory blood pressure (BP) was 180/100 despite maximum treatment dose of nifedipine and labetalol. Renal function, ECG, plasma renin/aldosterone ratio and urinary catecholamine study was normal. Renal ultrasound identified a small left kidney and after careful MDT discussion with detailed patient consent catheter renal angiography was performed. Radiation dose to the fetus was minimised by reducing the X-ray frame rate, exposure time and lead screening. Selective renal angiography demonstrated classical bilateral renal FMD and bilateral angioplasty resulted in excellent immediate results without complications. BP rapidly improved and the patient had a successful term delivery. Conclusions: Reports from the literature of FMD diagnosed in pregnancy are associated with poor pregnancy outcomes and there are few reports of antenatal angioplasty. FMD is a rare yet important diagnosis to exclude in women presenting with uncontrolled hypertension before fetal viability. In selected cases where the index of suspicion is high and after careful MDT discussion involving radiation protection specialists renal artery angioplasty can be effective in controlling BP. The longer-term risks to the child posed by antenatal radiation are small and outweighed by the greater, more immediate risk to mother and child during pregnancy of uncontrolled BP.